2015
DOI: 10.1371/journal.pntd.0003444
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Schistosomiasis and the Use of Human Waste as an Agricultural Fertilizer in China

Abstract: BackgroundHuman waste is used as an agricultural fertilizer in China and elsewhere. Because the eggs of many helminth species can survive in environmental media, reuse of untreated or partially treated human waste, commonly called night soil, may promote transmission of human helminthiases.Methodology/Principal FindingsWe conducted an open cohort study in 36 villages to evaluate the association between night soil use and schistosomiasis in a region of China where schistosomiasis has reemerged and persisted des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…We further investigated associations by adjusting for potential confounders, as well as child covariates, based on a priori knowledge of their association with both exposure and outcome. We conducted tests to evaluate linear trends in binominal proportions with increasing IDW well count by treating the categorical IDW well count variable as ordinal [ 38 ]. Specifically, covariates in our analysis were age category (0–4, 5–9, 10–14, 15–19, and 20–24 years) [ 1 , 4 ], race/ethnicity (white Hispanic, white non-Hispanic, non-white) [ 1 ], and gender [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…We further investigated associations by adjusting for potential confounders, as well as child covariates, based on a priori knowledge of their association with both exposure and outcome. We conducted tests to evaluate linear trends in binominal proportions with increasing IDW well count by treating the categorical IDW well count variable as ordinal [ 38 ]. Specifically, covariates in our analysis were age category (0–4, 5–9, 10–14, 15–19, and 20–24 years) [ 1 , 4 ], race/ethnicity (white Hispanic, white non-Hispanic, non-white) [ 1 ], and gender [ 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Zimbabwe, Chimbari et al [ 122 ] demonstrated that people working in the fields will not travel long distances to use their household latrines. Raw sewage is often used to fertilise crops, particularly in Asia [ 204 ], and this practice has sometimes been found to be associated with a greater risk of schistosome infection [ 205 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the issues associated is the intense foul odor and unhygienic conditions. There remains a threat of communicable disease or parasitic infections if the human excreta are improperly decomposed or mishandled (Oinam et al, 2008;Carlton et al, 2015). Moreover, heavy metals in human excreta are another issue that causes soil toxicity (Tervahauta et al, 2014;Harder et al, 2020).…”
Section: Human Excreta Compostingmentioning
confidence: 99%
“…There are reports of other countries using human excrement as a potential source for organic fertilizer (Low-tech magazine, 2010). Japan, China, and Sweden are some countries using human excrement as a source of fertilizer in agriculture (Low, 2013;Carlton et al, 2015;Akram et al, 2019). A study carried out in Sweden to enhance nutrient recycling from human and animal excrement reported that recycling excrement enhances plants' nutrient availability and could reduce the dependency on synthetic fertilizers and lead to sustainability (Akram et al, 2019).…”
Section: Human Excreta Compostingmentioning
confidence: 99%